Analisis Prediktor Rasio Keuangan Terbaik Terhadap Harga Saham Dengan Metode Best Subset Selection (Studi pada Perusahaan yang Terindeks di IDXHIDIV20 Bursa Efek Indonesia Periode 2018-2020) - Dedy Rahmat Saleh; Aisha Hanif; Hadiah Fitriyah; Sarwenda Biduri (Akuntansi : Jurnal Akuntansi Integratif, 2022)
This research aims to determine the effect of the best financial ratio predictors on stock prices of companies indexed on IDXHIDIV20 of Indonesian Stock Exchange for the 2018-2020 Period. This research used total population sampling as sampling method. The sample data were taken from 20 companies indexed on IDXHIDIV20 of Indonesian Stock Exchange for the 2018-2020 period. This research used secondary data. The analysis method in this research comprised best-subset selection for selecting the best financial ratio predictors till panel data regression to analyze the selected predictors supported by RStudio program. The results of this research show Earning Per Share (EPS) and Price to Earnings Ratio (PER) are selected as the best financial ratio predictors according to best-subset selection using Bayesian Information Criterion (BIC). Regarding the results of partial significance test, EPS positively influences stock prices and PER positively influences stock prices of companies indexed on IDXHIDIV20 of Indonesian Stock Exchange for the 2018-2020 Period.